Проблемні питання реалізації принципу субсидіарності в Україні - Мошак, О. В.; Moshak, Olena V. (Одеса : Гельветика, 2018)
У статті досліджено проблемні питання реалізації принципу субсидіарності в Україні. Утвердження зазначеного принципу є одним із ключових етапів приведення місцевого самоврядування України у відповідність до європейських стандартів. Сучасний же конституційний процес в Україні у питанні реформи місцевого самоврядування потребує не лише внесення змін до відповідного розділу Конституції, а й концептуального осмислення базових засад децентралізації публічної влади, оскільки належне застосування положень Основного Закону є невід’ємною ознакою демократичного розвитку правової держави, ефективного функціонування органів державної влади та органів місцевого самоврядування. One of the main European principles for the formation of the interaction of all levels of government is the principle of subsidiarity. In particular, this is defined in the European Charter of local self-government. The observing of the spirit and the letters of this document, generally accepted and binding on the member states of the Council of Europe, is extremely relevant in modern Ukraine. So, after the events of EuroMaydan, the new Government has launched a national project “Decentralization”, having approved on April 1, 2014 the Concept of reforming local self-government and territorial organization of power in Ukraine. The article deals with the problem- atic issues of implementing the principle of subsidiarity in Ukraine. The approval of this principle is one of the key steps in bringing local government in Ukraine in line with European standards. The modern constitutional process in Ukraine on the issue of the reform of local self-government requires not only amendments to the relevant section of the Constitution but also a conceptual understanding of the basic principles of the decentralization of public power, since proper application of the provisions of the Basic Law is an essential feature of the democratic development of a law-governed state, effective functioning bodies of state power and bodies of local self-government. In turn, laws must comply with the Constitution, rely on it as a prime cause. Therefore, without amending the Constitution, it is impossible to implement the reform of local self-government on the principles of decentralization. At the same time, constitutional changes are necessary to make this process irreversible.
Мошак О. В. Проблемні питання реалізації принципу субсидіарності в Україні / О. В. Мошак // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), І. В. Сафін (заст. голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2018. - № 5. – C. 98 – 112.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; Европейская Хартия местного самоуправления; субсидиарность; децентрализация; местное самоуправление; Конституція України; Європейська Хартія місцевого самоврядування; субсидіарність; децентралізація; місцеве самоврядування; subsidiarity; decentralization; local self-government; the European Charter of local self-government